Yield response of cassava Huay Bong 80 variety grown in an Oxyaquic Paleustult to cassava starch waste and nitrogen fertilizer - Phun-iam, Mutchima; Anusontpornperm, Somchai; Thanachit, Suphicha; Kheoruenromne, Irb (Agriculture and Natural Resources, 2018)
A field experiment was carried out in Na Yia district, Ubon Ratchathani province, Thailand during the 2015-2016 cropping season to investigate the response of cassava to cassava starch waste (CSW) and nitrogen (N). Split plots in a randomized completed block design with four replications were established in an Oxyaquic Paleustult soil type. The main plot consisted of five rates of CSW (0 t/ha, 6.25 t/ha, 12.5 t/ha, 25 t/ha or 50 t/ha). Six rates of N (0 kg/ha, 25 kg/ha, 50 kg/ha, 75 kg/ha, 100 kg/ha or 125 kg/ha) were applied to subplots. The addition of CSW at rates of 12.5 t/ha, 25 t/ha or 50 t/ha produced significantly higher fresh tuber and starch yields and starch content. The CSWapplied at the rate of 50 t/ha produced the significantly highest aboveground biomass, but with the lowest harvest index. Applying 75 kg/ha or 100 kg/ha of N produced significantly higher fresh tuber and starch yields. The respective highest fresh tuber and starch yields were obtained from the combination of 75 kg/ha of N and 12.5 t/ha of CSWas soil amendment. The concentrations of P, Ca, Mg, S and Zn in tubers significantly increased with increments of CSW. Furthermore, the CSW also significantly enhanced the nutrients stored in the topsoil after growing cassava for one crop.